2016
DOI: 10.15446/recolma.v49n2.60447
|View full text |Cite
|
Sign up to set email alerts
|

Multiplication operators in variable Lebesgue spaces

Abstract: In this note we will characterize the boundedness, invertibility, compactness and closedness of the range of multiplication operators on variable Lebesgue spaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Mursaleen et al [4], ˙Ilkhan et al [5] have studied multiplication operators on Cesàro function spaces. Further, Castillo et al [6][7][8], obtained significant results and modified the techniques used by the others to study multiplication operators on Orlicz-Lorentz spaces, weak L p spaces and variable Lebesgue spaces.…”
Section: Preliminaries Background and Notationmentioning
confidence: 99%
“…Mursaleen et al [4], ˙Ilkhan et al [5] have studied multiplication operators on Cesàro function spaces. Further, Castillo et al [6][7][8], obtained significant results and modified the techniques used by the others to study multiplication operators on Orlicz-Lorentz spaces, weak L p spaces and variable Lebesgue spaces.…”
Section: Preliminaries Background and Notationmentioning
confidence: 99%
“…The properties of the multiplication operator on measurable function spaces have been studied by numerous mathematicians. It is worth referring to the outstanding works of Abrahamese [6], Halmos [7], Takagi and Yokouchi [8] and Castillo, Rafeiro and Ramos-Ferández [9]. Recently, Castillo, Ramos-Fernández and SalasBrown [5] made a very comprehensive study about the properties of Mu acting on Köthe spaces.…”
Section: Proposition 1 the Multiplication Operator Mu Maps Bv[ ] Imentioning
confidence: 99%
“…Additionally, we note that the work of Arora et al in [4][5][6] examined properties of on Lorentz and Lorentz-Bochner spaces. Further significant results regarding multiplication operators were obtained by Castillo et al in [7][8][9], in which these authors showed that the techniques used by previously mentioned authors can be modified to study multiplication operators on weak spaces, Orlicz-Lorentz spaces, and variable Lebesgue spaces.…”
Section: Introductionmentioning
confidence: 98%